Fermentation Value Of Some Agro-Industrial Co-Products Based On Gas Production Kinetics With Dual Rate Constants (Applied Biological Research, 2018)
Ten agro-industrial co-products (AICP) viz., wheat (WB) and deoiled rice  (DORB), gram chuni of green gram (GGC) and hyacinth bean (HBC), husk  of Bengal gram (BGH), pigeon pea (PPH), hyacinth bean (HBH) and soy (SH)  and ground shells of groundnuts (GSL) and almond (ASL) were evaluated  for chemical composition and fermentation value (FV) aiding in the selection  of feedstuffs in dairy rations. Total carbohydrates in AICPs consisted of 55  to 80% of NDF and 20 to 25% of NFC. CP in DORB was 49% bound to ADF  but in other AICPs it was < 2.5%. Although macronutrient composition of  DORB was better than WB, FV of DORB was 50% lesser than WB. Among  husk, IVGP was higher in the order of HBH> SH> PPH> BGH which was  more related to hemicellulose content than other cell wall constituents.  Although fermentation rate of GSL and ASL were above 10% like WB, their  extent of fermentation was 75 to 85% lesser than WB. Brans fermentation  was ≥10% h-1 while gram chuni were fermented at a rate of 5 to 9% h-1.  Husk fermentation rate was slow (3 to 6% h-1). CO2 to methane ratio, extent  and rate of fermentation were critical kinetic attributes to differentiate FV of  AICPs. Net gas production of AICPs was greater with higher hemicellulose.  Studies conclude that NGP or hemicelluloses of brans, chunis, husks or shells  could be criteria for their selection to incorporate in dairy cattle ration.
Keywords: Brans; by-products; dairy; husks; nutrition; shells